Correlates of protection of serotype-specific capsular antibody and invasive Group B Streptococcus disease in South African infants. Issue 48 (27th November 2015) - Dangor, Ziyaad; Kwatra, Gaurav; Izu, Alane; Adrian, Peter; Cutland, Clare L.; Velaphi, Sithembiso; Ballot, Daynia; Reubenson, Gary; Zell, Elizabeth R.; Lala, Sanjay G.; Madhi, Shabir A.
Abstract: Background: Vaccinating pregnant women may prevent invasive Group B Streptococcus (GBS) disease in their young infants. In a low-middle income setting, we sought to determine an association between natural maternal antibody responses and the development of invasive GBS disease. Methods: We undertook a matched case-control study in Johannesburg, South Africa. Maternal and infant antibody concentrations were compared between serotype-specific Ia and III GBS cases and well-baby controls in which the mother was colonized with the same serotype. Results: The median maternal serotype Ia and III antibody concentrations (in μg/mL) were 0.05 (IQR: 0.02–0.24; n  = 27) and 0.14 (IQR: 0.08–0.33; n  = 29) in cases, and 0.29 (IQR: 0.06–1.60; n  = 43) and 0.29 (IQR: 0.13–0.58; n  = 31) in homotypic controls, respectively. A smaller proportion of cases as compared to homotypic controls had higher serotype Ia and III maternal antibody concentrations. Using Bayesian modeling, we demonstrated that the risk of invasive GBS disease was less than 10% with maternal antibody concentrations ≥6 μg/mL and ≥3 μg/mL for serotypes Ia and III, respectively. Conclusions: Maternal capsular antibody concentrations are associated with the risk of invasive GBS disease in infants. In a low-middle income setting with a high burden of invasive disease, we have demonstrated a sero-correlate of protection for GBS serotypes Ia and III which could facilitate vaccine licensure.